PROFESI AKUNTAN PEMERINTAH DI ‘ZAMAN NOW’: MASIHKAH MENARIK? - Tezza Abdu Isamah; Puji Wibowo (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2019)
Student perceptions towards accountant profession have been extensively discussed in many literatures. Along with an increase of central government financial reporting’s (LKPP) quality in Indonesia, bureaucratic sectors, on the other hand, are suffering from the lack of accountants. This research aims to investigate how regular students and civil servant students in Polytechnic of State Finance STAN (PKN STAN) perceive the government accountant profession. By using convenience sampling method, we found 208 respondents who answered our questionnaire adequately. This study suggests both groups agree that government accountants are still needed to support national budget accountability. Regular students are relatively motivated to be government accountants than officer students. Unexperienced students are better-off in knowledge about government accountants, while civil servant students have stronger motivation to permanently work in government sector than regular students. Staff placement policy in Line Ministries/Agencies to accommodate PKN STAN graduates becomes an interesting policy implication in upcoming years.